Mircea Eliade and René Guénon: Patterns of Initiation and the “Myth of Affinity” - Marino, Davide (Aries, 2024)
This article analyses the intellectual relationship between the historian of religions Mircea Eliade and the French esotericist René Guénon. Many scholars have argued for the “the myth of affinity”, a theory according to which Eliade would have subscribed to Guénon’s worldview (Traditionalism). The proponents of this thesis believe that Eliade opportunistically masked his Traditionalism for fear of being considered not sufficiently “scientific” for the academic career he aspired to. This article argues against such a theory and intends to demonstrate how the “myth of affinity” arose from a series of misunderstandings that occurred in the circle of Guénon’s closest associates, probably fuelled by Eliade himself. A comparison of Guénon and Eliade’s works on the theme of initiation will be used to dismiss “the myth of affinity” by indicating the irreconcilable theoretical distance between Traditionalism and Eliadian hermeneutics.